Sacred groves in conservation of biodiversity in Odisha - Taranisen Panda (The Holistic Approach to Environment, 2020)
Phytodiversity survey of sacred groves was carried out for a period of two years (2016-2018) in Bhadrak district of Odisha, India. A total of 42 plant species belonging to 39 genera under 26 families are recorded from 20 selected sacred groves of the district. Moraceae represents the dominant family. The respondents affirmed that the plants inside these sites are never cut or harmed and some plant like neem (Azadirachta indica A. Juss.), banyan (Ficus benghalensis L.) and peepal (Ficus religiosa L.) present in the sacred groves are more than a century old. The present study indicates the role of sacred groves in biodiversity conservation through faith, belief, religious activity and community participation.